Secondary consolidation of soft soils in salt-affected conditions related to sea lever rise, case study: hanoi soft soils - Vu, Nguyen Van; Truc, Nguyen Ngoc (Vietnam Journal of Earth Sciences, 2015)
In the scenario that inland areas along a coastline are affected by saline water, ground consolidation and deformation arechanged. The authors simulated the influence of saline intrusion to ground on geotechnical properties of soils by a case study of soft soils at 9 sites in Hanoi. Specimens were processed by making saturation with artificial seawater of four salt concentration levels, followed byexperiments using X-ray diffraction and one-dimensional consolidation. The results showed that the secondary consolidation is increased in the Hanoi salt-affected soft soils. The higher salt concentration of saturated solution is applied, the higher deformation occurred. This was interpreted based on clay minerals composition present in the soils. References Al-Shamrani M.A. & Dhowian A.W., 1996: Characterization of secondary compression behavior of Sabkhasoils. Engineering Geology 48 (1-2), 19-41. Azam S., 2000: Collapse and compressibility behavior of arid calcareous soil formations. Bulletin Eng. Geol. Env. 59, 211-217. Brouchkov A., 2003: Frozen saline soils of the arctic coast: their distribution and engineering properties. Proceedings - 8th International Conference on Permafrost, p. 95-100. Zurich, Switzerland. Dhowian A.W., 1991: Secondary compression of Sabkha saline soils. Engineering Geology 30, 155-169. Dương Thị Toan, Nguyễn Ngọc Trực, 2010: Ảnh hưởng của nước biển đối với các tính chất đất đồng bằng sông Hồng. Tạp chí Khoa học và Công nghệ, tr.215-223. Gbenga M. A., Oluwole A. A., Shodolapo O. F., 2009: Influence of Calcium Sulphate on Subsoil Cohesion and Angle of Friction. Journal of Applied Sciences Research, 5(3), 297-304. Germanov T. S., Kirov B. L., 1985: Influence of Waste Waters on Soil Consolidation, Proc. of XIth ICSMFE, A. A. Balkema, pp. 2407-2409. San Francisco, USA. Hideo K., 2007: Vulnerability of Riverbank Material by Sea Level Rising due to Global Warming in Japan. Proc. of the 2nd Malaysia-Japan Symposium on Geohazards and Geoenvironmental Engineering, pp. 209-212. Langkawi, Malaysia. James K. M., Kenichi S., 2005: Fundamentals of Soil Behavior, 3rd edition, Wiley. New York, USA. Kirov B. L., 1989: Influence of Waste Waters on Soil Deformation. Proc. of XII ICSMFE, pp. 1881-1882. Rio de Janeiro, Brazil. Kirov B. L., Truc N. N., 2012: A Study on the Relationship between Geotechnical Properties and Clay Mineral Composition of Hanoi Soft Soils in Saline Media. Inter. Journal of Civil Engineering, Vol. 10 (2), pp. 87-92. Mesri G., Godlewski P. M., 1977: Time and Stress Compressibility Interrelationship, Journal of Geotechnical Engineering, ASCE, 105 (1), pp.106-113. Mesri, G., 1973: Coefficient of Secondary Compression, Journal of Soil Mech. and Found. Div., 99(1), pp.123-137. Rashid M. A., Buckley D. E., Robertson K. R., 1972: Interactions of a marine humic acid with clay minerals and a natural sediment. Geoderma,<a href="http://www.sciencedirect.com/science?_ob=PublicationURL&_tockey=%23TOC%235807%231972%23999919998%23415695%23FLP%23&_cdi=5807&_pubType=J&view=c&_auth=y&_acct=C000050221&_version=1&_urlVersion=0&_userid=10&md5=9d44ecca036ceb65227db7320e09c286">Vol. 8 (1), pp. 11-27. Truc N. N., Granie R. J., 2008: Global Warming - Related Sea Level Rise and The Change of Some Mechanical Characteristics of Soil Foundation Due to Salty Intrusion, Case Study Thai Binh Formation Sediment in The RRD, Vietnam. In: Giao PH, editor, Proc. of Int. Sym. on Climate Change and the Sustainability, pp. 131-140. Hanoi, Vietnam. Truc N. N., Hung D. N., 2007: The Issue of Sea Level Rise Due to Global Warming and Its Impacts on The Coastal Zone of Vietnam. In: Giao PH, editor, Proc. of Int. Sym. on Hanoi Geoengineering, pp.124-130. Hanoi, Vietnam. Van Hoorn J. W., Van Alphen J. G., 1994: Salinity Control. In Ritzema HP editor. Drainage Principles and Applications, ILRI Publication 16 (2nd edition), pp. 533-600. Wageningen, The Netherlands. Yeliz Y. A., Kaya A., Ören A. H., 2008: Seawater Effect on Consistency Limits and Compressibility Characteristics of Clays, Engineering Geology, pp. 54-61.